영릉향으로부터 분리된 Foenumoside B의 부위별 함량비교 연구 - 엄영란(Young Ran Um); 목소연(So Youn Mok); 신재혁(Jae Hyuck Shin); 김슬기(Seul Ki Kim); 조병헌(Byoung Heon Cho); 조용백(Yong Baik Cho) (생약학회지, 2014)
Lysimachia foenum-graecum (LF) has been used for home remedy of common cold and headache in China. Foenumoside B from LF has been reported for anti-obesity effects. We used foenumoside B as a marker for content evaluation of different parts of LF. Ethanol extract of LF was used for isolation of foenumoside B and purified further by column chromatography. The structure was identified as foenumoside B by interpretation of spectroscopic analysis, including $^1H$-, $^{13}C$-NMR and FT-ICR-MS. High-performance liquid chromatography (HPLC) method was used to compare the quantitative level of foenumoside B in different parts of LF. Foenumoside B contents in the leaf, stem, and aerial part showed significant differences. Contents of foenumoside B was detected highly in the leaf extracts. The results would be useful for efficient extraction of foenumoside B in LF.